Leptolegnia chapmanii como alternativa biológica para el control de Aedes aegypti - Rueda Páramo, Manuel Enrique (2019)
Leptolegnia chapmanii is a facultative pathogen of many species of mosquitoes, among which species of the genus Aedes, Culex and Anopheles stand out for their medical and sanitary importance. The potential of L. chapmanii as an alternative to control lies in its virulence, pathogenicity and specificity against the larval stages of mosquitoes, and because of its harmlessness to non-target species such as fish and amphibians, among others. The natural presence of L. chapmanii had been reported in Argentina, Brazil and the United States. Its presence is possible in other countries throughout the American continent. The development of protocols to produce, formulate, store and apply products based on this microorganism is one of the objectives proposed for the group of Entomopathogenic Fungi at the Centro de Estudios Parasitologicos y de Vectores, Universidad Nacional de La Plata. The efficacy of L. chapmanii as controller is affected by external factors such as temperature, pH, salinity and radiation among others. The process of transfer from the research centers to industry implies many phases. In this way, our project with L. chapmanii is in an initial phase, where we are working on a laboratory scale in proof of concept. We hope to begin soon with the efficacy, efficiency, stability and ecotoxicological safety tests, at the laboratory, semi-field and field scale.